If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2b + 8b + 3x = 0 Reorder the terms: -2b + 8b + 9x + 3x = 0 Combine like terms: -2b + 8b = 6b 6b + 9x + 3x = 0 Combine like terms: 9x + 3x = 12x 6b + 12x = 0 Solving 6b + 12x = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-12x' to each side of the equation. 6b + 12x + -12x = 0 + -12x Combine like terms: 12x + -12x = 0 6b + 0 = 0 + -12x 6b = 0 + -12x Remove the zero: 6b = -12x Divide each side by '6'. b = -2x Simplifying b = -2x
| 3(4x+1)-2(2x-7)=73 | | 70-(3Q+70)=70-4Q | | 4x+5x-2=16 | | 4.5+y=y-5.5 | | 16x+17=73 | | X-(-2-x)=-2(-2x-4) | | 6x+5y=1650 | | 8=(y/3=3/4) | | 17u=48+9u | | −1/2s−7 | | (3n-6)-(4n-8)= | | 6.28r=3.14r^2 | | (2x^2+y)dy+(x^2y-x)dx=0 | | 3-(x+5)=2(x+3)-7 | | -84=-7(2m+6)+8m | | 1.5x+(18-1.5x)=18 | | X^3-125/5x-5 | | (5x+14y)+(3x+3y)= | | 700=464+7x | | -51+3= | | 7u-9=3u+5 | | X^3-135/5x-5) | | 3t-8=-11 | | x/3-6=10 | | y-18+y+x=180 | | 7x-5=-2x+4 | | -2y+14=3x | | 6h+5(3)=45 | | 5x+3(x-4)+12=2(4x+3) | | 2x+14=3x-31 | | 9r-9=-342 | | 4/3x-10=24 |